How to use Adobe Premiere 6.5 - Dixon, Douglas (Douglas F.) (Que, 2003)
How to Use Adobe Premiere 6.5 is the fastest and easiest way to get started with Premiere, whether you're new to video editing or stepping up to Premiere's professional features from another tool. With its color screenshots and straightforward descriptions, this book shows you all you need to know to effectively use Premiere to make your own video productions, including titles, transitions, and special effects. You also learn how to save your video productions in streaming video formats that facilitate sharing across the Internet or to burn to DVD.